Evaluation of Growth Performances and Meat Quality of Tunisian Local Poultry Raised in Outdoor Access - Raach-Moujahed, A.; Haddad, B.; Moujahed, N.; Bouallegue, M. (International Journal of Poultry Science, 2011)
Local and indigenous poultry in Tunisia represent very diversified and heterogeneous populations which remain largely unknown and understudied in spite of the real economic assets that they seemed to represent mainly in rural areas. The present study was envisaged in the objective of conservation, valorization and development of this rustic and well adapted genetic substrate. In this respect growth parameters were measured and meat quality measurements on pH and color (L*: luminance, a*: yellowness b*: redness) were operated. Results showed that a mean Body Weight (BW) of 632 g was reached at week 8, 923 g at week 12 and 1249 g at week 16, with mean Daily Weight Gain (DWG) of 16.72, 11.26 and 10.89 g/d respectively. Males were found to be more (p<0.05) performing than females both in BW and DWG at all ages. The ultime meat pH value after 24 h of slaughtering was relatively high (6.1) and color parameters in the main muscles were particularly intense. Feed Conversion Ratio (FCR) was relatively low (3.97) and remained far lower than several other local populations studied in some European and African countries. It was concluded that Tunisian local poultry presented potentially interesting growth parameters and meat quality characteristics. In addition to the high potential of selection and crosses possibilities, they could represent a strong argument of development of local production systems for rural populations. Thereby, an urgent program of screening, evaluation and conservation of these populations is to be conceived and applied.